1993
DOI: 10.1111/j.1439-0396.1993.tb00804.x
|View full text |Cite
|
Sign up to set email alerts
|

Urinary excretion of pseudouridine and purine metabolites in ruminants

Abstract: Zusammenfassung Die Ausscheidung von Pseudouridin und Purin‐Metaboliten über den Harn beim Wiederkäuer In einem ersten Versuch wurde Hefe‐RNA bei drei Kühen über zwei Tage in Mengen von 0 (Kontrolle), 30, 50 und 70 g d‐1 in das Duodenum infundiert. Die Ausscheidung von Pseudouridin wurde durch die Infusion von RNA nicht beeinflußt und betrug 19,80, 20,62, 20,32 und 19,71 μmol kg W0.75 d‐1 bei der Kontrolle und nach der Infusion von 30, 50 und 70 g d‐1 Hefe‐RNA. Die durchschnittliche Wiederfindungsrate der infu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
2

Year Published

1997
1997
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 15 publications
(4 reference statements)
2
14
2
Order By: Relevance
“…There was no much difference in the body weight of the animals used in this study and they had similar excretion of urinary creatinine. The daily mean urinary creatinine excretion observed was lower than previous reports of between 112 to 117 mmol/d in European cattle (Puchala et al, 1993). It is conceivable that between breed/species differences in musculature and variations in body weight could account for these discrepancies.…”
Section: Purine Derivatives and Creatinine In Urine And Plasma At Difcontrasting
confidence: 75%
“…There was no much difference in the body weight of the animals used in this study and they had similar excretion of urinary creatinine. The daily mean urinary creatinine excretion observed was lower than previous reports of between 112 to 117 mmol/d in European cattle (Puchala et al, 1993). It is conceivable that between breed/species differences in musculature and variations in body weight could account for these discrepancies.…”
Section: Purine Derivatives and Creatinine In Urine And Plasma At Difcontrasting
confidence: 75%
“…Urinary concentrations of pseudouridine (Table 1) were similar to the 2.2 mmol/day of the non-lactating cows measured by Puchala et al (1993); however, plasma pseudouridine concentrations were not in the range of Rosskopf et al (1991), who found 0.006 ± 0.0016 mmol L − 1 circulating in bovine blood plasma. The cattle used in the study of Rosskopf et al (1991) were milking cattle and not rapidly growing beef steers, and this may account for the discrepancy.…”
Section: Discussionsupporting
confidence: 50%
“…Pseudouridine is a nucleoside isomer of uridine that exists in ribonucleic acids as a carbon-carbon linked ribonucleside on the TφC arm of transfer RNA (tRNA) (Lehninger, 1982) and it is released without further processing when tRNA is degraded (Weissman et al, 1962). Puchala et al (1993) validated the use of pseudouridine as an indicator of tRNA degradation by showing that infusion of RNA into the rumen did not increase its excretion in the urine over 24 h. Although not a specific indicator of tRNA degradation in skeletal muscle, the amount of pseudouridine excreted in urine over 24 h is useful as a metabolic indicator of whole body protein synthesis.…”
mentioning
confidence: 97%
“…Urinary allantoin has been studied more thoroughly in domestic ruminants, whose 24-h excretion was also positively correlated with energy intake over short time periods when there was little change in physical condition (Chen et al 1990a(Chen et al , 1990b(Chen et al , 1992Verbic et al 1990;Giesecke et al 1993Giesecke et al , 1994Puchala et al 1993). Cattle and sheep fed maintenance diets have shown pronounced species differences in endogenous allantoin excretion, and the effects of short-term fasting on allantoin excretion have been inconsistent Faichney 1964a, 1964b;Rys et al 1975;Antoniewicz and Pisulewski 1982;Fujihara et al 1987;Chen et al 1990aChen et al , 1990bPuchala and Kulasek 1991).…”
Section: Introductionmentioning
confidence: 99%